Natural Polymer Chitosan as Super Disintegrant in Fast Orally Disintegrating Meloxicam Tablets: Formulation and Evaluation - Gailute Draksiene; Brigita Venclovaite; Lauryna Pudziuvelyte; Liudas Ivanauskas; Mindaugas Marksa; Jurga Bernatoniene (MDPI AG, 2021)
The aim of the present investigation was to formulate fast disintegrating tablets of meloxicam by wet granulation technique using medium molecular weight chitosan. The orally disintegrating tablets of meloxicam with chitosan showed good mechanical and disintegration properties and good dissolution rate when prepared in tablet press using 10.8 kN and 11.0 kN compression force. Chitosan is a suitable biopolymer to moderate the disintegration process in orally disintegrating tablets.